Turkey’s Attitude in the Present Geopolitical Juncture. - Ioannis Mazis (Contribution à Institut Jean Lecanuet, 2014)
The Turkish political leadership of Davutoğlu-Erdoğan (in this hierarchical order) is fully aware of the gradual erosion of Turkey’s strategic value for the West in general and for NATO specifically. This erosion is attributed to geophysical factors, i.e. the melting of ice along the Northeastern Passage (Bering Strait). This geophysical development shall allow in a few years Russia’s approach to the strategic points of the Pacific Ocean in a timeframe that shall be three times faster in comparison to the US. This fact is expected to undermine in due time the strategic importance of Turkey as a containment factor (along with Greece) of Russian expansion into the warm waters of the Mediterranean. It also reduces significantly the overall strategic role of NATO’s Southeastern Wing, a role which is promoted under the moral-ideological cover of ‘GreekTurkish friendship’. This ‘Greek-Turkish friendship’ is continually challenged by Ankara in the Aegean Sea and in the Exclusive Economic Zone (EEZ) of Cyprus. We should also note that 38% of the territory of Cyprus Republic, a member-state of the European Union, is still under Turkish occupation.